The role of mathematics education in shaping sustainable futures: A systematic literature review - Lina, Sri Intan; Johar, Rahmah; Anwar (Universitas Hamzanwadi, 2025)
The integration of Sustainable Development Goals (SDGs) into mathematics education has gained increasing attention in recent years. This study systematically reviews how mathematics contributes to sustainability and aligns with the SDGs. A systematic literature review (SLR) was conducted following the PRISMA guidelines, analysing 31 studies published between 2019 and 2024 from databases such as EBSCO, ERIC, ProQuest, and Taylor & Francis. Content analysis identified key themes, including the SDGs addressed, educational levels, and research methodologies. The findings indicate that most studies focus on SDG 4 (Quality Education) and SDG 13 (Climate Action), primarily in primary and secondary schools. Qualitative and mixed-methods approaches are commonly used, with project-based learning as a frequently applied instructional model. The review confirms that mathematics education plays a vital role in fostering critical thinking, problem-solving, and sustainability awareness. However, challenges persist in terms of curriculum development and teacher training. Future research should explore interdisciplinary approaches and expand the integration of diverse SDGs into mathematics education to strengthen its role in addressing global sustainability challenges.